2019
DOI: 10.1111/tbed.13173
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a virulent porcine reproductive and respiratory syndrome virus in Taiwan in 2018

Abstract: SummaryIn March 2018, an abortion storm caused by porcine reproductive and respiratory syndrome virus was confirmed in a farrow‐to‐finish pig herd in Taiwan. Open reading frame 5 and non‐structural protein 2 of the virus confirmed that the virus is closely related to the virulent strains circulating in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Overall, the genetics of PRRSV in Asian countries have been dynamic. Independent evolution [12], transmission among Asian countries, introduction of novel PRRSV strains from outside Asia [13,14] and recombination between PRRSV strains [15] were all involved. Moreover, use of PRRS modified live virus (MLV) vaccines could also impact PRRSV genetic variation and the ongoing genetic changes of PRRSV [16] .…”
Section: Prrsvmentioning
confidence: 99%
“…Overall, the genetics of PRRSV in Asian countries have been dynamic. Independent evolution [12], transmission among Asian countries, introduction of novel PRRSV strains from outside Asia [13,14] and recombination between PRRSV strains [15] were all involved. Moreover, use of PRRS modified live virus (MLV) vaccines could also impact PRRSV genetic variation and the ongoing genetic changes of PRRSV [16] .…”
Section: Prrsvmentioning
confidence: 99%
“…Previous reports show that prevalence rates of PRRSV-1 and PRRSV-2 were 29.4%, 38.4% (2007–2008), 51% and 54.4% (2013–2016), 37.4%, and 49% (2014–2019) [ 14 , 27 , 30 ]. It has been confirmed that both PRRSV-1 and PRRSV-2 coexist on swine farms in South Korea, which were similar to those in China, Hungary, and Taiwan [ 14 , 27 , 30 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 68%
“…The open reading frame 5 (ORF5) genes were amplified and sequenced as described in a previous study [26]. The nucleotide sequences were determined from both orientations by an ABI 3730XL DNA analyzer (Applied Biosystems, Foster City, CA).…”
Section: Open Reading Frame 5 Amplification and Sequencingmentioning
confidence: 99%